Hypertension Predisposition and Thermoregulation Delays in Adolescents with Polycystic Ovary Syndrome: A Pilot Study - Styliani Geronikolou; Flora Bacopoulou; Stavros Chryssanthopoulos; Dennis V. Cokkinos; George P. Chrousos (MDPI AG, 2022)
Background: Polycystic ovary syndrome (PCOS) is a heterogeneous disorder in which clinical, sonographic, and endophenotypic features have been underinvestigated or inconclusive, especially in the early stages of the disease (adolescence/young adulthood). Objective: This prospective pilot study focused on the differences of multiple physiological functions between Greek adolescent/young adult females suffering from PCOS and age- and body mass index (BMI)- matched healthy controls. Study design: Nineteen PCOS patients and eighteen healthy controls (aged 13 to 23 years) were studied for: (i) biochemical and hormonal dysfunction by measuring circulating glucose, insulin, and androgen levels; (ii) arterial stiffness with pulse wave analysis (PWA) by Sphygmocord; (iii) intima-media thickness (IMT) by ultrasound; (iv) heart rate variability (HRV) by Task Force Monitor; and (v) QT, QRS, QT, P, QRSD by electrocardiogram (ECG). Statistical analysis included Hedge's g correction for small samples bias, and the results are shown using the Hedge's g effect size and 95% CI, in line with precision medicine prerequisites. Results: Significant differences in pulse wave velocity (PWV) (g = 0.964 [0.296, 1.632]), subendocardial viability ratio (SEVR) carotid (g = −0.679 [−1.329, −0.030]), pulse pressure (PP) carotid (g = 0.942 [0.275, 1.608]), systolic pressure (SP) carotid (g = 0.785 [0.129, 1.440]), free-testosterone (g = 0.677 [0.042, 0.312]), and Delta4-androstenedione (g = 0.735 [0.097, 0.373]) were observed between PCOS patients and controls. No differences were detected in the remaining endocrine and PWA or ECG biomarkers. Conclusions: Our multidisciplinary approach showed early onset of vascular dysfunction, predisposition to hypertension, thermoregulation delays, and metabolic syndrome changes in adolescent/young adult PCOS.